Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Effect of Alignment on a Liquid Crystal/Split-Ring Resonator Metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (ChemPhysChem)

Polycyclic Aromatic Hydrocarbons Obtained by Lateral Core Extension of Mesogenic Perylenes: Absorption and Optoelectronic Properties - Vollbrecht, Joachim; Bock, Harald; Wiebeler, Christian; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (Chemistry - A European Journal)

Polymer-stabilized blue phases: promising mesophases for a new generation of liquid crystal displays - Nordendorf, G.; Hoischen, A.; Schmidtke, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Synthesis of Liquid Crystal Silane-Functionalized Gold Nanoparticles and Their Effects on the Optical and Electro-Optic Properties of a Structurally Related Nematic Liquid Crystal - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Nanoparticle Doping in Nematic Liquid Crystals: Distinction between Surface and Bulk Effects by Numerical Simulations - Urbanski, Martin; Mirzaei, Javad; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Planar anchoring strength and pitch measurements in achiral and chiral chromonic liquid crystals using 90-degree twist cells - McGinn, Christine K.; Laderman, Laura I.; Zimmermann, Natalie; Kitzerow, Heinz-Siegfried; Collings, Peter J. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Alfred Saupe Prize 2013 Laudatio for Prof. Dr Gerd Heppke* - Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Measurement of group velocity dispersion in a solid-core photonic crystal fiber filled with a nematic liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Liquid crystal assisted optical fibres - Wahle, M.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Tunable infrared resonance spectra of split ring resonators embedded in a liquid crystal - Atorf, B.; Muhlenbernd, H.; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (2013 7th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics)

Photonic Micro- and Nanostructures, Metamaterials - Kitzerow, Heinz-Siegfried (Handbook of Liquid Crystals)

Real-time coherent detection of phase modulated ultrashort pulses after time-to-space conversion and spatial demultiplexing - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.